Climate change awareness and adaptation by rice farmers in Surallah, South Cotabato - Baron, Jomarie V. (Goodwood Publishing, 2024)
Purpose: This study aimed to assess the level of awareness and extent of adaptation strategies of upland and lowland local rice farmers in the municipality of Surallah, in the province of South Cotabato, in response to the impacts of climate change. Methodology/approach: This study utilized a descriptive-correlational research design to evaluate the awareness levels, extent of adaptation strategies, and interrelationships among these variables within upland and lowland local rice farming communities in Surallah, South Cotabato province. Results/Findings: The research findings highlight the significant differences in awareness levels and adaptation strategies between upland and lowland rice farmers. Upland farmers exhibited lower awareness and sporadic adaptation measures, while their lowland counterparts demonstrated a moderately aware status with a corresponding, albeit moderate, application of adaptive strategies. The study also revealed a meaningful positive relationship between awareness levels and adaptation strategies across both groups. Limitations: The study focused only on the municipality of Surallah in the Province of South Cotabato, concentrating on upland and lowland farmers. Contribution: The findings of this study reveal how farmers in different geographical settings respond to the challenges presented by climate change and reveal potential connections between awareness and adaptation strategies, which will become the basis for policy recommendations. Novelty: The novelty of this study lies in its specific focus on upland and lowland rice farmers in Surallah, South Cotabato, providing a comprehensive examination of awareness and adaptation strategies towards climate change.